Settlement of The Conflict Between The Republic of The Philippines and The People's Republic of China Through The Permanent Court of Arbitration - Fikri Ardiyansyah; Jeremias Adams; Thomas Adams; Amalia Amaya Navarro (International Journal of Science and Environment (IJSE), 2025)
The purpose of this study is to explain the background of the resolution of the South China Sea conflict between the Republic of the Philippines and the People’s Republic of China through the Permanent Court of Arbitration. This thesis is grounded in a fundamental framework of thought that combines international security theory and international legal theory. In searching for data sources, the researcher employed a qualitative method. The results of this study explain that the international arbitration decision confirms that the islands claimed by China do not meet the requirements for a right to an exclusive economic zone (EEZ) or a wide continental shelf. The Philippines is considered the rightful owner of the area included in its exclusive economic zone in accordance with UNCLOS. In addition, this decision emphasizes that China’s actions in building islands and placing infrastructure in the disputed area violate the rights of the Philippines and the principles of international law. In addition, based on the author’s interviews with the Ministry of Foreign Affairs, the results indicate that the South China Sea conflict between the Chinese and Philippine governments is a latent issue that is very difficult to resolve.